Quantum Cryptography in Advanced Networks - Morozov, Oleg G. (IntechOpen, 2019)
Proposed 35 years ago, quantum cryptography (QC) and its most prominent part quantum key distribution (QKD) attracts more and more attention. Significant progress has been made in both its theory and practice from many points of view. The present book has four exclusive chapters. All chapters are focused on QC and QKD applications in advanced telecommunication networks: classical fiber optic lines with a constant increase in the range of quantum communication channels and duration of the connection; software-defined optical networks; free-space optical communication systems; and systems with elements of holographic processing. The book will be useful for researchers, engineers, and doctoral students working in areas of QC, QKD, and related areas of information security.